Моделювання фотонно кристалічних хвилеводів та їх оптимізація - Сологуб, М. К. (ХНУРЕ, 2025)
In this work, two schemes of photonic crystal waveguides are considered. These waveguides are formed by linear defects of periodicity, which performs the function of a channel. A dielectric plate and a chain of dielectric cylinders were used. Simulation and theoretical investigation of the photonic crystal waveguides are performed with using of free packages MIT Photonic Bands and MEEP. Dispersion characteristics, spatial distributions of the electromagnetic field components and spectral characteristics are calculated for different values of waveguide systems parameters.
Keywords: фотонно-кристалічний хвилевід; моделювання хвилеводів